TINGKAT KERAWANAN BENCANA BIOLOGIS DEMAM BERDARAH DENGUE (DBD) DENGAN PENDEKATAN SPASIAL DI KABUPATEN BOMBANA - Osu Oheoputra Husen; Erny Tamburaka (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
The study analyzed the spread of dengue (DHF) susceptibility index based on the incidence rate (IR). This research was conducted in Bombana Regency, Southeast Sulawesi Province. The study used a quantitative design. The object of analysis is the number of cases, the frequency and the index of vulnerability. Data were analyzed using descriptive qualitative and spatial analysis (ArcView 3.2). DHF cases in Bombana Regency are spread across six sub-districts and 35 villages / wards. Poleang Barat 208 cases, Poleang 111 cases, South Poleang 64 cases, East Poleang 46 cases, Rumbia 24 cases and Middle Rumbia 17 cases. There are 12 villages / kelurahan with the status of “very vulnerable”, 6 which are “vulnerable”, 2 which are “somewhat vulnerable”, 8 which are “somewhat safe” and 7 villages / kelurahan that are “safe”. The average number of DHF cases that occur is around 0.33-0.98% of the total population. It was found that the ages of 0-10 years (48.30%), 11-20 years (28.09%). Infecting men as much as 49.57% and 50.43% women.